The Use of a Respiratory Biofeedback Instrument in Managing Fear and Anxiety in Clinical Practice - Natalie Sui Miu Wong; Andy Wai Kan Yeung; Colman Patrick McGrath; Yiu Yan Leung (International Dental Journal, 2025)
Introduction and aims: Fear and anxiety are commonly experienced across diverse healthcare settings globally, particularly in clinical practices where these emotions tend to be heightened due to the nature of the procedures. This single-blinded, randomized controlled trial aimed to investigate the effectiveness of a respiratory biofeedback instrument in reducing state and dental anxiety levels during dental extractions in adult patients. Methods: The trial design and reporting adhered strictly to the CONSORT statement guidelines. Patients were randomly assigned to either the biofeedback group (n = 30) or the control group (n = 30). State anxiety levels were measured using pulse rate, respiratory rate, respiratory regularity, respiratory amplitude, Visual Analogue Scale (VAS) scores, and the State-Trait Anxiety Inventory (STAI). Dental anxiety was assessed using the Modified Dental Anxiety Scale (MDAS), and Dental Fear Survey (DFS). Results: Results demonstrated that the biofeedback group had a significantly lower state anxiety level during dental extraction, as evidenced by lower respiratory rate (mean difference = –2.75 bpm, P = .03), higher respiratory regularity (5.63%, P = .035) and higher respiratory amplitude (48.83 units, P = .005). The biofeedback group also had a significantly lower STAI-State score after dental extraction (–2.04, P = .015), and a larger reduction in pulse rate from the time of extraction to after extraction (–3.61 bpm, P = .030). However, biofeedback implementation did not significantly affect dental anxiety levels, as measured by the MDAS and DFS. Conclusions: This study highlights the potential benefits of employing on-site biofeedback instruments to alleviate anxiety during dental extractions in adult patients without the need for multiple training sessions. Clinical relevance: Further research is needed to explore its impact on dental anxiety levels and investigate its applicability to a broader range of dental procedures.